FACTORS THAT MAKE EXCLUSIVE BREASTFEEDING DIFFICULT - Flávia Freitas de Miranda Coêlho, Ana; Taynara Xavier Rodrigues, Maria; da Silva Fidelis, Laysa; Rodrigues Vieira, Edineia; Michele de Araujo Pedro, Fabiana; Claudino do Nascimento, Nathalia; Carolina Salustino, Maria (Health and Society, 2023)
Objective: to identify in the scientific literature factors that hinder exclusive breastfeeding. Development: This is an integrative literature review, which took place between June and July in the Scientific Electronic Library Online (SciELO) and in the databases: Latin American Literature of the Caribbean in Health Sciences (LILACS) and Bases de nursing data (BDENF); in LATINDEX (Regional Online Information System for Scientific Journals of Latin America, the Caribbean, Spain and Portugal), and Red Iberoamericana (REDIB), through the Virtual Health Library (VHL). Results: It showed the main factors that hinder the practice of exclusive breastfeeding, among them are: pain, the appearance of fissures, mastitis, the mother’s return to work, difficulty in “handling”, lack of guidance, little experience of mom. Conclusion: The study becomes essential in conducting practices to encourage exclusive breastfeeding in the prevention of early weaning.